2011
DOI: 10.1088/0004-637x/740/2/107
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Hydrodynamic Simulations of Massive Star Formation With Protostellar Outflows

Abstract: We report the results of a series of AMR radiation-hydrodynamic simulations of the collapse of massive star forming clouds using the ORION code. These simulations are the first to include the feedback effects protostellar outflows, as well as protostellar radiative heating and radiation pressure exerted on the infalling, dusty gas. We find that outflows evacuate polar cavities of reduced optical depth through the ambient core. These enhance the radiative flux in the poleward direction so that it is 1.7 to 15 t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
272
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 156 publications
(281 citation statements)
references
References 84 publications
(116 reference statements)
8
272
1
Order By: Relevance
“…In general, potential driving mechanisms include supernova explosions and expanding radiation fronts and shells induced by high-mass stellar feedback (McKee 1989;Balsara et al 2004;Krumholz et al 2006;Breitschwerdt et al 2009;Goldbaum et al 2011;Peters et al 2011;Lee et al 2012), winds , gravitational collapse and accretion of material (Vazquez-Semadeni et al 1998;Elmegreen & Burkert 2010;Klessen & Hennebelle 2010;Vázquez-Semadeni et al 2010;Federrath et al 2011b;Robertson & Goldreich 2012;Lee et al 2015), and Galactic spiral-arm compressions of H I clouds turning them into molecular clouds (Dobbs & Bonnell 2008;, as well as magnetorotational instability (MRI) and shear (Piontek & Ostriker 2007;Tamburro et al 2009). Jets and outflows from young stars and their accretion disks have also been suggested to drive turbulence (Norman & Silk 1980;Matzner & McKee 2000;Banerjee et al 2007;Nakamura & Li 2008;Cunningham et al 2009Cunningham et al , 2011Carroll et al 2010;Wang et al 2010;Plunkett et al 2013Plunkett et al , 2015Federrath et al 2014;Offner & Arce 2014). While different drivers may play a role in different environments (such as in spiral-arm clouds), Kruijssen et al (2014) found that most of these drivers are not sufficient to explain the turbulent velocity dispersions in the CMZ.…”
Section: Turbulence Driving?mentioning
confidence: 99%
“…In general, potential driving mechanisms include supernova explosions and expanding radiation fronts and shells induced by high-mass stellar feedback (McKee 1989;Balsara et al 2004;Krumholz et al 2006;Breitschwerdt et al 2009;Goldbaum et al 2011;Peters et al 2011;Lee et al 2012), winds , gravitational collapse and accretion of material (Vazquez-Semadeni et al 1998;Elmegreen & Burkert 2010;Klessen & Hennebelle 2010;Vázquez-Semadeni et al 2010;Federrath et al 2011b;Robertson & Goldreich 2012;Lee et al 2015), and Galactic spiral-arm compressions of H I clouds turning them into molecular clouds (Dobbs & Bonnell 2008;, as well as magnetorotational instability (MRI) and shear (Piontek & Ostriker 2007;Tamburro et al 2009). Jets and outflows from young stars and their accretion disks have also been suggested to drive turbulence (Norman & Silk 1980;Matzner & McKee 2000;Banerjee et al 2007;Nakamura & Li 2008;Cunningham et al 2009Cunningham et al , 2011Carroll et al 2010;Wang et al 2010;Plunkett et al 2013Plunkett et al , 2015Federrath et al 2014;Offner & Arce 2014). While different drivers may play a role in different environments (such as in spiral-arm clouds), Kruijssen et al (2014) found that most of these drivers are not sufficient to explain the turbulent velocity dispersions in the CMZ.…”
Section: Turbulence Driving?mentioning
confidence: 99%
“…This implies that most of the kinetic energy of the jets is lost to radiation, and to a good approximation the jets may be considered as sources of momentum only, i.e., are of the momentum-conserving case (Krumholz et al 2014). When hot massive stars are presence, ionizing radiation, radiation pressure, and stellar winds play a larger role than jets launched by YSOs in the feedback mechanism in star forming clouds (e.g., Smith et al 2010;Cunningham et al 2011;Krumholz et al 2014). When only low and medium mass stars are formed, jets have more pronounced role.…”
Section: Young Stellar Objects (Ysos)mentioning
confidence: 99%
“…We use the high-resolution versions of these simulations, which have finest cells of 23 AU. Once gas is Jeans unstable even at this resolution, we replace it with an accreting sink particle (Krumholz, McKee & Klein 2004) that is coupled to a protostellar evolution calculation (Offner et al 2009) and injects radiation and winds (Cunningham et al 2011) back into the computational domain. The accretion process removes mass but not magnetic flux from the computational domain, and thereby decreases the mass to flux ratio inside the accretion region around the sink particle.…”
Section: Summary Of the Simulationsmentioning
confidence: 99%